Pengaruh Durasi Pneumotorak Terhadap Tingkat Stress Oksidatif Paru Tikus Wistar - Faisal Muttaqien; Bermansyah Bermansyah; Irsan Saleh (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTLarge pneumothorax with long duration of symptoms can be dangerous. Large pneumothorax can cause hypoxemia and its duration states the duration of hypoxia. This long duration of hypoxia can affect changes in tissue conditions of the lungs, which if it reaches 72 hours can increase the permeability of the alveolar capillaries in the lungs to facilitate pulmonary edema. Large pneumothorax with long duration of symptoms can be a risk factor for re-expansion pulmonary edema (REPE). Meanwhile, hypoxia can also cause increased production of free radicals in lung tissue (pulmonary oxidative stress). This study investigated whether the duration of pneumothorax also affects the level of pulmonary oxidative stress, with experiments in rats. There were 4 groups consisting of 6 rats in each group: 24 hours of pneumothorax (A), 48 hours of pneumothorax (B), 72 hours of pneumothorax (C) and control (D). Pneumothorax is made by injecting air into the right pleural cavity of the chest, then we performed X-ray. All samples were examined for PaO2 to ensure hypoxia status. After that, the rats were examined for malondialdehyde (MDA) levels to express the level of oxidative stress. The result showed that all pneumothorax groups were hypoxemic (PaO2 below 80 mmHg). Mean MDA levels were higher in pneumothorax groups. However, only group C were significantly higher (p=0,031). MDA levels were 1,601 ± 0,739 in group A, 1,585 ± 0,714 in group B, 2,256 ± 0,513 in group C, and 1,243 ± 0,162 in group D. We concluded that pneumothorax can cause pulmonary oxidative stress if the pneumothorax has a large volume and the duration of symptoms reaches 72 hours.Keywords : Pneumothorax, REPE, Lung Edema, Free Radicals, Malondialdehyde, Hypoxia.Correspondance to : faisaldanyani@gmail.com ABSTRAKPneumotorak luas dengan durasi gejala yang lama dapat berbahaya. Pneumotorak luas dapat menyebabkan hipoksemia dan durasi gejalanya yang lama menyatakan durasi hipoksia parunya. Durasi hipoksia ini dapat mempengaruhi perubahan kondisi jaringan di paru, yang bila mencapai 72 jam dapat meningkatkan permeabilitas kapiler alveolar di paru sehingga memudahkan terjadinya edema paru. Pneumotorak luas dengan durasi gejala yang lama dapat menjadi faktor resiko reexpansion pulmonary edema (REPE). Sementara itu, hipoksia juga dapat menyebabkan peningkatan produksi radikal bebas di jaringan paru (stress oksidatif paru). Penelitian ini menginvestigasi apakah durasi pneumotorak juga mempengaruhi tingkat stress oksidatif paru, dengan eksperimen pada tikus. Terdapat 4 kelompok yang masing-masing terdiri dari 6 tikus: kelompok pneumotorak 24 jam (A), pneumotorak 48 jam (B), pneumotorak 72 jam (C) dan kontrol (D). Pneumotorak dibuat dengan cara injeksi udara ke rongga pleura dada kanan, lalu di X-ray. Semua sampel diperiksa PaO2 untuk memastikan tingkat hipoksianya. Setelah itu, tikus diperiksa kadar malondialdehid (MDA) parunya untuk mengetahui tingkat stress oksidasi parunya. Hasil penelitian menunjukkan semua kelompok tikus pneumotorak mengalami hipoksemia. Rata-rata kadar MDA lebih tinggi pada kelompok pneumotorak, namun secara statistik hanya bermakna pada kelompok 72 jam (C) dengan p=0,031. Kadar MDA pada masing-masing kelompok adalah 1,601 ± 0,739 pada kelompok A, 1,585 ± 0,714 pada kelompok B, 2,256 ± 0,513 pada kelompok C, dan 1,243 ± 0,162 pada kelompok D. Kesimpulannya pneumotorak dapat menyebabkan stress oksidatif paru bila pneumotorak bervolume luas dan durasi gejala mencapai 72 jam.Kata kunci: Pneumotorak, REPE, Edema Paru, Radikal Bebas, Malondialdehid, HipoksiaKorespondensi : faisaldanyani@gmail.com